Meningkatkan Kemampuan Menulis Teks Eksplanasi Menggunakan Model Pembelajaran Kooperatif Tipe Berpikir-Berpasangan-Berbagi (Think-Pair-Share) Pada Siswa Kelas XI MAS Tanjungjaya Cihampelas KBB - Irani Pratiwi (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
This research is motivated by the lack of interest of students in writing which is caused by the difficulty of students expressing the ideas and ideas that exist in their minds. This study aims to improve students' abilities in expressing the ideas that students have in writing explanatory texts. In addition, the study was conducted to determine the effect of the think pair share model on students' explanatory text writing skills. Researchers conducted research using experimental methods with a design uasi experimental design nonequivalent control group design. The population taken is class XI MAS Tanjungjaya and the sample taken is class XI MAS Tanjungjaya, amounting to 18 people. The results of the implementation of teacher learning are 96% and the implementation of student learning is 94% meaning that the teacher is able to carry out learning well and students respond well to learning using the TPS model. The results showed an increase in learning in writing explanatory text using the TPS model in class XI MAS Tanjungjaya students, with an average score of 47 in the pre-test and 77 for the final test.